Position of Whistleblower and Justice Collaborator In Corruption Crime - Suisno Suisno; Enik Isnaini (Universitas Islam Lamongan, 2021)
This research is aims to know the arrangement of whistleblowers Jo Juctise collaborator in no criminal corruption other than that this article also aims to find out enforcement of whistleblower jo juctise collaborator in no criminal corruption, Using a normative juridical method of study can be concluded, that in the arrangement of whistleblower jo juctise collaborator in no criminal corruption is obvious to any witnesses and victims of legal arrangements against whistleblower jo juctise collaborator Collaborato in criminal acts can be concluded that is tetera in the law only the protection of witnesses and victims is set in law number 13 year 2006 and Whtleblower and Justice Collaborato set in the SEMA No 4 year 2011corruption. The enforcement of whistleblower and justice Collabolator still uses weights in the Law No. 20 of 2001 on the Eradication of corruption and is also in the case of SEMA to strengthen the protection of witnesses and victims.